Confined Lennard-Jones potential: a variational treatment - Silva, F. R. [UNESP]; Drigo Filho, Elso [UNESP] (World Scientific Publ Co Pte Ltd, 2010)
In this work, the energy eigenvalues for the confined Lennard-Jones potential are calculated through the Variational Method allied to the Super symmetric Quantum Mechanics. Numerical results are obtained for different energy levels, parameters of the potential and values of confinement radius. In the limit, where this radius assumes great values, the results for the non-confined case are recovered..
Keywords: Variational method; confinement; Lennard-Jones potential